Financial Distress Prediction In Non-Cyclical Sector Companies - Dian Putri Christiani (Mega Aktiva, 2024)
Financial distress is a signal for companies to avoid bankruptcy. Analysis of financial ratios is very important for company stakeholders in dealing with rapid economic changes. For example, the Corona pandemic that emerged in 2020 caused several companies to experience financial distress, including primary consumer sector companies. The companies under study that experienced financial distress included Bumi Teknoculture Unggul Tbk., Eagle High Plantations Tbk., and Tri Banyan Tirta Tbk. This study uses linear regression analysis with leverage, liquidity, profitability and activity as independent variables, while the dependent variable financial distress is proxied in the calculation of the Altman Z-Score. The result of this study is that leverage has a negative effect on financial distress. Liquidity does not prove that there is an effect on the dependent variable while profitability and activity have a positive effect on financial distress.